2017
DOI: 10.1016/j.ebiom.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for Differential Long-term Outcomes of Early Life Severe Acute Malnutrition

Abstract: BackgroundSevere acute malnutrition (SAM) in infants may present as one of two distinct syndromic forms: non-edematous (marasmus), with severe wasting and no nutritional edema; or edematous (kwashiorkor) with moderately severe wasting. These differences may be related to developmental changes prior to the exposure to SAM and phenotypic changes appear to persist into adulthood with differences between the two groups. We examined whether the different response to SAM and subsequent trajectories may be explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…We deliberately focused on differences incurred in the context of acute starvation, such that the molecular changes described are specific to the acute pathology of ESAM, and relative to NESAM. This differentiates our study from previous studies of more general malnutrition that are agnostic to the form of SAM 29,30 . Similarly, by integrating molecular correlates of expression and assessing the contribution of cis- acting genetic variation, we provide a unique view of this gene-environment response that may hold lessons for other disorders.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…We deliberately focused on differences incurred in the context of acute starvation, such that the molecular changes described are specific to the acute pathology of ESAM, and relative to NESAM. This differentiates our study from previous studies of more general malnutrition that are agnostic to the form of SAM 29,30 . Similarly, by integrating molecular correlates of expression and assessing the contribution of cis- acting genetic variation, we provide a unique view of this gene-environment response that may hold lessons for other disorders.…”
Section: Discussioncontrasting
confidence: 45%
“…Genes implicated in our ESAM study showed little-to-no overlap with those noted in a previous study of methylation in adult survivors of malnutrition 29 ; however, that study did not include the severity or type of SAM, and primarily focused on whole blood samples, making direct comparisons difficult. Nonetheless, it may be that the underlying mechanisms postulated here are still relevant—mitotic turnover among growing children is typically higher than in adults; and, whereas buccal epithelium is dynamically replenished, other cell types demonstrate less continuous renewal, allowing aberrations in methylation incurred during childhood to be perpetuated in tissues such as heart or muscle, potentially leading to the long-term health consequences that have been associated with the divergent SAM phenotypes 30,69,70 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic analysis of skeletal muscle biopsies identified significant differences in methylation over 133 CpG loci. These loci included genes implicated in glucose metabolism, body size and body composition [68], lending biological plausibility to the findings.…”
Section: (C) Predictive Adaptive Responses In Humansmentioning
confidence: 67%
“…A general trend towards reduced promoter methylation levels of genes involved in energy metabolism, myogenesis, contractile activity, and oxidative stress resistance became apparent when global methylation patterns in skeletal muscle of healthy aged men with a lifelong history of physical activity were compared to “couch potatoes” of the same age group (Sailani et al, 2019). Reciprocally, also “bad memories” inflicted by physical inactivity, unhealthy diet, and prenatal stress have been reported to become reflected by differential DNA methylation patterns in skeletal muscle tissue (Alibegovic et al, 2009; Jacobsen et al, 2012; Jacobsen et al, 2014; Nilsson & Ling, 2017; Nitert et al, 2012; Sharples, Polydorou et al, 2016; Sheppard et al, 2017).…”
Section: Skeletal Muscle Exercise and Flexible Epigenomementioning
confidence: 99%